Alterations of naïve and memory B‐cell subsets are associated with risk of rejection and infection in heart recipients. (10th June 2013) - Lanio, Nallibe; Sarmiento, Elizabeth; Gallego, Antonio; Calahorra, Leticia; Jaramillo, María; Navarro, Joaquin; Palomo, Jesus; Fernandez‐Yañez, Juan; Ruiz, Manuel; Fernandez‐Cruz, Eduardo; Carbone, Javier
Abstract: Rejection and infection are relevant causes of mortality in heart recipients. We evaluated the kinetics of the maturation status of B lymphocytes and its relationship with acute cellular rejection and severe infection in heart recipients. We analyzed B‐cell subsets using 4‐color flow cytometry in a prospective follow‐up study of 46 heart recipients. Lymphocyte subsets were evaluated at specific times before and up to 1 year after transplantation. Higher percentages of pretransplant class‐switched memory B cells (CD19+CD27+IgM‐IgD‐ >14%) were associated with a 74% decrease in the risk of severe infection [Cox regression relative hazard (RH) 0.26, 95% confidence interval (CI), 0.07–0.86; P = 0.027]. Patients with higher percentages of naïve B cells at day 7 after transplantation (CD19+CD27‐IgM+IgD+ >58%) had a 91% decrease in the risk of developing acute cellular rejection (RH 0.09; 95% CI, 0.01–0.80; P = 0.02). Patients with infections showed a strong negative correlation between baseline serum B‐cell–activating factor (BAFF) concentration and absolute counts of memory class‐switched B cells ( R = −0.81, P = 0.01). The evaluation of the immunophenotypic maturation status of B lymphocytes could prove to be a useful marker for identifying patients at risk of developing rejection or infection after heart transplantation.